Factors influencing quality of life and predictors of low quality of life scores in patients on treatment for pulmonary tuberculosis: a cross sectional study. - Olufunke O. Adeyeye; Olayinka O. Ogunleye; Ayodele Coker; Yetunde Kuyinu; Raymond T. Bamisile; Udeme Ekrikpo; Babatunde Onadeko (AOSIS, 2014)
There is paucity of information on the quality of life of patients with pulmonary tuberculosis in Nigeria. This study assessed the factors influencing their quality of life and the independent predictors of low quality of life scores. Two hundred and sixty consecutive patients with pulmonary tuberculosis seen at the Lagos University Teaching Hospital were evaluated for health related quality of life using the World Health Organization Quality of life instrument (WHOQoL-BREF). Sociodemographic characteristics of the patients were related to the various domains of quality of life and a multivariate logistic regression analysis was performed to identify the independent predictors of low quality of life scores in the patients. The mean age of the patients was 36.7±12 years. Sex, age and marital status of patients were found to influence quality of life scores. The independent predictors of low quality of life scores were low monthly income, duration of the illness, concomitant illnesses, unemployment, advancing age and male gender. Several socio demographic and economic factors influenced the quality of life of patients with tuberculosis and are predictive of poor scores. It is important to consider these factors when treating patients with tuberculosis to optimise outcome of care.